ANALYSING CYBERCRIME UNDERGROUND ECONOMY USING DATA ANALYTICS - G, Nandini; N, Abhishek; M, Akash Raju; K A, Chandan; S, Navneeth (The journal of contemporary issues in business and government, 2021)
Given the rapid acceleration of digital hazards, little work has been carried out into the subject's institutions or procedures that could help to guide scientists and specialists in Information Systems that handle digital security. There is also no discussion of Crime as a Service that is a criminal action program which facilitates decentralized cyber-crime. The examination whole and useful cyber- crime issue that we see has persuaded us to research underground cybercrime economy by adopting information research strategy from a scientific point of view of the structure. To accomplish this objective, we will propose 1. a structure to information investigation to break down the underground cyber-crime, 2. CaaS and product definitions for wrong-doing and 3. a model for related order. Furthermore, 4. Create a software web-app to show how the proposed system and request structure can really be actualized. At that point, we will use web applications to explore the under-ground economy of cyber-crime by breaking down a huge data-set from the web-based network. In implementing the strategy- based structure science review, this review applies objects, institutions, and strategies to the project here. It also gives professional expertise to recommend rules on how governments and associations can plan underground cybercrime assaults in all businesses.